Looking for Justice for the People: A Book Review Keadilan Restoratif, Yoachim Agus Tridiatmo, 2016, 83 Pages, Cahaya Atma Pusaka ISBN 9786027821491 - Erlangga, Nova (Faculty of Law, Universitas Negeri Semarang, 2021)
In the first chapter of this book the author presents a summary of several cases that intersect with justice that have occurred in Indonesia. One summary of a case of justice that has occurred and has received a lot of attention is the case of the father of the senses who traveled 900 kilometers which took 22 days to go to the Indonesian capital, Jakarta to meet with President Susilo Bambang Yudhoyono. He decided to meet with President Susilo Bambang Yudhoyono because he wanted to present the case of injustice, he had received for 15 years.